Implementing Professional Midwife-Led Maternity Care in India for Healthy Pregnant Women: A Community Case Study - Beckingham, Andy; Downe, Soo; Fernandez, Evita; Reed, Becky; Kaur, Indie; Aziz, Nuzhat; Kingdon, Carol (Frontiers in Public Health, 2022)
More women and neonates die each year in India than in almost every other country of the world. Since at least 1947, India has, in principle, provided free medical maternal health care to all pregnant and childbearing women. Although rates of maternal and neonatal deaths have fallen since the 1990s, major inequalities remain. Some Indian states have very high rates of interventions, such as caesarean section, while others have intervention rates and rates of care utilization that are too low. Disrespectful treatment of women in labour and lack of evidence-based practice have also been reported. The World Health Organisation and others have strongly recommended that professional midwives (trained in a woman-centred philosophy and to international standards) have a key role for reducing mortality and morbidity, minimising unnecessary interventions in pregnancy and labour, and improving maternal care quality in low- and medium-income countries. This paper provides a community case-report of the first professional midwifery programme in India designed to international standards, implemented in 2011 in Hyderabad. We describe the design and implementation in the programme’s first eight years, as a basis for further scale-up and testing in India, and in other low- or medium-income countries. The ultimate aim is to improve maternal care quality, choice and outcomes in India and in similar socio-economic and cultural settings.